2015
DOI: 10.1016/j.sjbs.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Escherichia coli O157:H7 recovered from meat and meat products relevant to human health in Riyadh, Saudi Arabia

Abstract: Raw meat can harbor pathogenic bacteria, potentially harmful to humans such as Escherichia coli O157:H7 causing diarrhea and hemolytic-uremic syndrome (HS). Therefore, the current study was carried out to evaluate the prevalence and the molecular detection characterization of E. coli serotype O157:H7 recovered from raw meat and meat products collected from Saudi Arabia. During the period of 25th January 2013 to 25th March 2014, 370 meat samples were collected from abattoirs and markets located in Riyadh, Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 23 publications
4
25
1
Order By: Relevance
“…Zarei et al (2013) [25] reported that the prevalence of E. coli O157:H7 in the meat samples of beef, buffalo and lamb were 2.8%, 1.4% and 0%, respectively which was entirely lower than our findings. Hessain et al (2015) [26] reported that the prevalence of E. coli O157:H7 in raw beef, chicken and mutton meat samples were 2%, 2.5% and 2.5%, respectively which was lower than our findings. They showed that the prevalences of E. coli O157:H7 in ground beef, beef burgers, beef sausage, ground chicken and chicken burgers were 5%, 10%, 0.0%, 5% and 0.0%, respectively.…”
Section: Discussioncontrasting
confidence: 93%
“…Zarei et al (2013) [25] reported that the prevalence of E. coli O157:H7 in the meat samples of beef, buffalo and lamb were 2.8%, 1.4% and 0%, respectively which was entirely lower than our findings. Hessain et al (2015) [26] reported that the prevalence of E. coli O157:H7 in raw beef, chicken and mutton meat samples were 2%, 2.5% and 2.5%, respectively which was lower than our findings. They showed that the prevalences of E. coli O157:H7 in ground beef, beef burgers, beef sausage, ground chicken and chicken burgers were 5%, 10%, 0.0%, 5% and 0.0%, respectively.…”
Section: Discussioncontrasting
confidence: 93%
“…The result of this study agrees with the 74%, 57.9% and 43% prevalence of E. coli found from beef in South Africa, Colombia and Burkina Faso respectively [2123]. However, a low prevalence of 1-4% and 2.8% of E. coli was reported in the city of Graz, Saudi Arabia and Amatole district of the Eastern Cape Province, South Africa respectively [24,25]. Both studies mainly focused on E. coli O157: H7, hence the differences in both studies could easily be explained given the very low levels of prevalence of E .…”
Section: Discussionsupporting
confidence: 88%
“…Xia et al [18] conveyed the higher incidence (23.50%) of E. coliin turkey meat samples. Furthermore, boost incidence of E. coli O157 in meat samples was reported by Hossain et al [19] (Saudi Arabia) (2-10%), De Giusti et al [20] (Italy) (2.61%), Momtaz et al [5] (Iran) (25-36%) and Ranjbar et al [3] (Iran) (25-34%). The incidence of E. coli O157 in meat samples demonstrated to be changeable in various areas owing to variation in number of livestock, season of sampling, hygienic circumstances in each farm, levels of farm management, sampling oddness, discrepancy in kind of samples, and departure in methods of pathogenic detection.…”
Section: Discussionmentioning
confidence: 79%